Exegesis and Authorial Agency through Judeo-Christian Iconography in Japanese Anime: Neon Genesis Evangelion (1995-97) as an Open Work - Sellés de Lucas, Víctor; Hernández-Pérez, Manuel (Imafronte, 2024)
Exegesis is a common practice when discussing religious texts. It has also been employed in the analysis of cultural production to elucidate the author's intentions. Japanese animation (anime) is a transnational industry with cases such as Neon Genesis Evangelion (1995-1997), in which the figure of an individual author, in this case the filmmaker Hideaki Anno, interacts with the collaborative authorship by the rest of the production team. The extensive use of obscure Judeo-Christian terminology and iconography in this work has risen debate about the actual intentions of Japanese author(s) when referring to Western culture. Our analysis concludes that the use of this iconography is intentional. The ambiguity of the narrative, shaped using multiple obscure references, aims to induce in the viewer the feeling of a complex text. This would reinforce the previous considerations of this anime as an "open work", in the sense defined by post-structural semiotic analysis.